THE EFFECT OF TRUST AND JOB SATISFACTION ON ORGANIZATIONAL CITIZENSHIP BEHAVIOR - Thurayah,; Murni, Sylviana; Widodo, Suparno Eko (International Journal of Psychosocial Rehabilitation, 2020)
The objective of this research was to understand the effect of trust and job satisfaction on organizational citizenship behavior. It was quantitative research in twenty-two (22) Senior High Schools located in Makassar district, Sulawesi Selatan, Indonesia.The research used a survey method with path analysis applied in the testing hypothesis. It was conducted to 292 teachers as the respondents who were selected in a simple random way.The result of this study are: (1). There is a positive direct effect of trust on organizational citizenship behavior. (2).There is a positive direct effect of job satisfaction on organizational citizenship behavior, and (3). There is a positive direct effect of trust on job satisfaction.